The Relationship Between rs3779084 in the Dopa Decarboxylase (DDC) Gene and Alcohol Consumption is Mediated by Drinking Motives in Regular Smokers - Kristjansson, Sean D. (2011)
BACKGROUND: Motivational models of alcohol use propose that the motivation to consume alcohol is the final common pathway to its use. Both alcohol consumption and drinking motives are influenced by latent genetic factors that partially overlap. This study investigated whether drinking motives mediate the associations between alcohol consumption and 2 single-nucleotide polymorphisms (SNPs) from genes involved in serotonin (TPH2; rs1386496) and dopamine synthesis (DDC; rs3779084). Based on earlier work showing that enhancement and coping motives were heritable in regular smokers but not in nonregular smokers, we hypothesized these motives would mediate the relationships between alcohol consumption and these SNPs in regular smokers. METHODS: Drinking motives data were available from 830 young adult female twins (n = 344 regular smokers and n = 486 never/nonregular smokers). We used confirmatory factor analyses to model enhancement, coping, and alcohol consumption factors and to conduct mediation analyses in the regular smoker and never/nonregular smoker groups. RESULTS: Our hypothesis was partially supported. The relationship between alcohol consumption and rs1386496 was not mediated by drinking motives in either group. However, in the regular smokers, the relationship between alcohol consumption and rs3779084 was mediated by enhancement and coping motives. Carriers of the rs3779084 minor allele who were regular smokers reported more motivation to consume alcohol. Given this pattern of results was absent in the never/nonregular smokers, our results are consistent with a gene × smoking status interaction. CONCLUSIONS: In regular smokers, variability at the locus marked by rs3779084 in the DDC gene appears to index biologically based individual differences in the motivation to consume alcohol to attain or improve a positive affective state or to relieve a negative one. These results could be because of increased sensitivity to the reinforcing effects of alcohol among minor allele carriers who smoke, which might be due to structural or functional differences in mesorticolimic dopamine “reward” circuitry.